The blood-brain barrier and CNS drug development - Stanimirovic, Danica (Henry Stewart Talks, 2008)
Restrictive nature of the blood-brain barrier, Non-vascular routes for brain drug delivery, Vascular routes for brain drug delivery, Concept of Trojan horses, Discovery of novel receptor-mediated transcytosis routes across the blood-brain barrier, Principles of blood-brain barrier vector development in experimental models